2020
DOI: 10.3390/genes11121493
|View full text |Cite
|
Sign up to set email alerts
|

Tensor-Decomposition-Based Unsupervised Feature Extraction Applied to Prostate Cancer Multiomics Data

Abstract: The large p small n problem is a challenge without a de facto standard method available to it. In this study, we propose a tensor-decomposition (TD)-based unsupervised feature extraction (FE) formalism applied to multiomics datasets, in which the number of features is more than 100,000 whereas the number of samples is as small as about 100, hence constituting a typical large p small n problem. The proposed TD-based unsupervised FE outperformed other conventional supervised feature selection methods, random for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…• We have successfully used the region length [49,50]. When started to employ this procedure, we tried multiple values and identified that it is most successful.…”
Section: Plos Onementioning
confidence: 99%
“…• We have successfully used the region length [49,50]. When started to employ this procedure, we tried multiple values and identified that it is most successful.…”
Section: Plos Onementioning
confidence: 99%
“…Tensor decompositions provide a natural framework for integrating heterogeneous omics data types. By decomposing the multi-omics tensor, tensor decomposition techniques can reveal shared and specific patterns across different data sources, enabling the identification of cross-modal relationships and uncovering novel insights [20].…”
Section: Omics Datamentioning
confidence: 99%
“…The article, [20] proposes a novel approach for predicting the progression of Alzheimer's disease using MRI (Magnetic Resonance Imaging) data. The method leverages tensor multi-task learning, which is a machine learning technique that jointly learns multiple related tasks to improve performance.The authors focus on capturing both spatial and temporal characteristics of the MRI data.…”
Section: Canonical Polyadic (Cp)mentioning
confidence: 99%
See 2 more Smart Citations